2020
DOI: 10.1186/s12903-020-01108-4
|View full text |Cite
|
Sign up to set email alerts
|

3D assessment of mandibular skeletal effects produced by the Herbst appliance

Abstract: Background: A functional appliance is commonly used to optimize the development of the facial skeleton in the treatment of Class II malocclusion. Recent three-dimensional(3D) image-based analysis offers numerous advantages in quantitative measurement and visualization in orthodontics. The aim of this study was to localize in 3D the skeletal effect produced by the Herbst appliance on the mandible using the geometric morphometric technique. Methods: Twenty patients treated with a Herbst appliance and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…CBCT has not been frequently used in the evaluation of condylar response to functional orthopaedic therapy in patients with skeletal Class II malocclusion [ 23 , 24 ]. However, only recently, CBCT was used for the 3D assessment of mandibular and glenoid fossa changes [ 13 , 14 , 25 , 26 ]. It has been demonstrated that CBCT provides accurate and reliable linear measurement of the TMJ dimensions of dry human skulls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT has not been frequently used in the evaluation of condylar response to functional orthopaedic therapy in patients with skeletal Class II malocclusion [ 23 , 24 ]. However, only recently, CBCT was used for the 3D assessment of mandibular and glenoid fossa changes [ 13 , 14 , 25 , 26 ]. It has been demonstrated that CBCT provides accurate and reliable linear measurement of the TMJ dimensions of dry human skulls.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Herbst appliance treatment stimulated the condylar growth in the vertical direction [ 32 ]. The three-dimensional evaluation of skeletal mandibular changes following Herbst appliance have also shown greater 3D superior and posterior condylar growth than in their control group, resulting in significant mandibular forward displacement without pitch [ 14 , 26 , 33 ]. In the evaluation of changes in condylar volume, an average increase of 297 mm 3 was reported in both the right and left condylar volumes in response to functional therapy with the twin block appliance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the robust Procrustes alignment algorithm, the pointwise surface-to-surface distance between the original and mirror models in 3D space was calculated, which was expressed as the overall asymmetry index (AI). The position and severity of mandibular asymmetry are shown by a color map in millimeters [ 4 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fibrocartilage covering its surface has strong remodeling and repair capacity, which provides a physiological basis for using functional orthodontic appliances to promote condylar growth and change the position of the mandible [38]. Fan et al analyzed the morphology of the condyle before and after treatment with functional orthodontic appliances in 20 adolescent patients with Class II malocclusion and found that the sagittal length of the condyle increased by 1.5-3.0 mm after treatment [39]. Wei et al also found that the use of functional orthodontic appliances in adolescent patients with Class II malocclusion resulted in the adaptive growth in the upper and posterior parts of the condyle [40].…”
Section: Condyle Growth and Displacementmentioning
confidence: 99%